2019
DOI: 10.1016/j.cell.2019.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Ligands Antagonize Estrogen Receptor Function by Impairing Its Mobility

Abstract: Highlights d Drug candidates optimized for ER degradation can weakly activate ER in cancer cells d ''ER degraders'' trigger interaction of ER with DNA at canonical binding sites d Impact on chromatin accessibility distinguishes ER antagonists from weak activators d Dramatic slowing of ER mobility drives ER antagonism, and precedes ER turnover

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
145
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 68 publications
(68 reference statements)
10
145
0
Order By: Relevance
“…These data raise the question whether the current path(s) of SERD development place unnecessary emphasis on potent and efficient downregulation of the receptor without equal attention to the efficacy of ER inhibition independent of receptor degradation. Furthermore, a recent study has reported that the efficacy of fulvestrant and additional SERDs are mediated by their ability to slow receptor mobility as opposed to their ability to downregulate ER [42]. In essence, the imperative to develop a SERD may result in the unnecessary omission of potentially tolerable complete antagonists and/or high affinity SERMs.…”
Section: Discussionmentioning
confidence: 99%
“…These data raise the question whether the current path(s) of SERD development place unnecessary emphasis on potent and efficient downregulation of the receptor without equal attention to the efficacy of ER inhibition independent of receptor degradation. Furthermore, a recent study has reported that the efficacy of fulvestrant and additional SERDs are mediated by their ability to slow receptor mobility as opposed to their ability to downregulate ER [42]. In essence, the imperative to develop a SERD may result in the unnecessary omission of potentially tolerable complete antagonists and/or high affinity SERMs.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of these differences in ER target gene activation remain to be explored but could suggest that cross-resistance between different classes of SERDs can be avoided. Recent studies have indicated that in addition to receptor degradation, ER mobility is differentially impacted by sub-classes of SERMs and SERDs, and that compounds impeding mobility are more efficacious antagonists [35]. The impact of G1T48 on ER mobility is not currently known; however, our studies establish that G1T48 has very low intrinsic ER agonist activity.…”
Section: Discussionmentioning
confidence: 51%
“…The most active SERDs share common chemical features: either (a) a steroidal backbone (e.g., fulvestrant, RU58,668) or (b) an acrylic acid side chain (GW7604, GDC-0810, AZD9496) [29,31,32,40,56,57]. Additional ER antagonists with novel chemical structures have also been reported to exhibit SERD properties [35,36,58], but none has yet gained FDA approval and some have been discontinued due to adverse effects or for undisclosed reasons [29-36, 40, 56]. We have identified a novel, orally bioavailable SERD, G1T48, that contains both a steroidal backbone and an acrylate side chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCR ligand: G protein-coupled receptors, also includes Dopamine D3(So et al, 2020)  Ion channel modulator: Ion channel modulator, is a type of drug that can modulates ion channels(Churchill et al, 2019)  Kinase inhibitor: Represent a type of enzyme inhibitor that can block the action of a protein kinases. Protein kinases are enzymes that add a Phosphate (PO4) group to a protein and can modulate its function(Xie et al, 2020)  Nuclear receptor ligands: Are active proteins in the nucleus of cells(Guan et al, 2019)  Enzyme inhibitor: Is a substance that binds to an enzyme to decrease its activity  Protease inhibitors: Are a class of antiviral drugs used in the treatment of HIV(Zhang et al, 2019b) The chemical structure of metoclopramide…”
mentioning
confidence: 99%